Caracterização estrutural do Lineamento de Piúma e sua influência na porção norte da Bacia de Campos - Bronzoni, Letícia Cornachini [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The detailed study of the Brazilian continental margin basins became possible with the advancement of geophysical tools, with emphasis on seismic reflection. Characterizing the structural and stratigraphic elements of Brazil’s marginal basins they realized that there was a relationship with structures present on the adjacent continental basement. So many works began to be made to understand this relationship and know the major factors that influenced the evolution of the continental margin. The study area of this work includes the northern portion of the Campos Basin and the continental outcropping adjacent areas, which corresponds to the northern of Rio de Janeiro state and the southern of Espirito Santo state. This area stands an important structural feature of NW-SE direction with a projection to the Campos Basin called Lineamento de Piúma. The outcropping basement rocks belongs to the Ribeira Belt which was bonded to other mobile bands forming the continent Western Gondwana during the Brasiliano Cycle, which later fragmented giving rise to the Atlantic Ocean. The opening of the ocean results on the formation of the marginal basins of Brazil. These basins have continental, transitional and marine facies. On Campos Basin the continental phase resulted on the formation of horsts and grabens bounded by synthetic and antithetic faults. Continuing rifting formed the saline lakes that deposited siliciclastic and carbonate sediments. The transitional phase resulted on thick packages consist of evaporites (halite and anhydrite) that was deposited in lagoon environment, tectonically quiet arid and semi-arid. The marine phase it deposited siliciclastic and carbonate in the Campos Basin resulting in shales, marls, limestones, ritmito, turbidites, sandstones and others. The objective of this study is to investigate the possible continuation... (Complete abstract click electronic access below)

O estudo detalhado das bacias da margem continental brasileira se tornou possível com o avanço das ferramentas geofísicas, com destaque para a sísmica de reflexão. Ao caracterizar o arcabouço tecno-estratigtáfico das bacias marginais do Brasil, observou-se uma relação com estruturas presentes no embasamento continental adjacente. Assim vários trabalhos começaram a ser feitos para buscar a fim de entender esta relação e conhecer os principais condicionantes que influenciaram a evolução da margem continental. A área de estudo do presente trabalho compreende a porção norte da Bacia de Campos e a porção continental aflorante nas áreas adjacentes, que corresponde ao norte do estado do Rio de Janeiro e o sul do estado do Espírito Santo. Nesta área destaca-se uma feição estrutural de direção NW-SE com projeção para a Bacia de Campos denominada de “Lineamento de Piúma”. As rochas do embasamento aflorante pertencem à Faixa Ribeira que foi aglutinada a outras faixas móveis durante o Ciclo Brasiliano formando o continentel Gondwana Ocidental, que mais tarde fragmentou-se dando origem ao Oceâno Atlântico. A abertura do oceano gerou as bacias marginais que possuem fácies continentais, transicionais e marinhas. A fase continental da Bacia de Campos deu origem a horsts e grábens limitados por falhas sintéticas e antitéticas. Ao continuar o rifteamento formaram-se lagos salinos que depositaram sedimentos siliciclásticos e carbonáticos. A fase transicional deu origem aos espessos pacotes de evaporitos compostos por halita e anidrita e foi depositado em ambiente lagunar, tectonicamente calmo e de clima árido a semi-árido. Na fase marinha depositaram-se sedimentos siliciclásticos e carbonáticos na Bacia de Campos dando origem a folhelhos, margas, calcários, ritmitos, turbiditos, arenitos e outros. O objetivo do presente trabalho... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Sismologia; Sensoriamento remoto; Geologia estrutural; Campos, Bacia de (RJ); Seismology; Remote sensing; Geology, Structural